The Role of Si3N4 Amorphous Phase in nc-TiN/a-Si3N4 Nanocomposites in Increases the hardness and Thermal Stability - Moto, Keba (Makara Journal of Technology, 2002)
The role of Si3N4 amorphous phase in nc-TiN/a-Si3N4 nanocomposites will be shown and compared with polycrystalline ZrN/Ni which has no such amorphous phase (non-composites). The presence of amorphous phase Si3N4 increases the hardness of film as well as the toughness of the bulk nanocomposites under indentation load. It has been observed that nc-TiN/a-Si3N4 nanocomposites films has higher thermal stability than ZrN/Ni polycrystalline films.